Beyond Test Scores: Using Drawings and Language Samples to Characterize Multilingual Children's Language Profiles - Bazzocchi, Nicole B. M.; Kokotek, Leslie E.; Crowe, Kathryn; Washington, Karla N. (Seminars in Speech and Language, 2025)
The United Nations Conventions on the Rights of the Child highlight the importance of children being involved in matters that concern them. Examining children's drawings can support speech-language pathologists' understanding of children's unique communication experiences, especially when considered alongside a language sample analysis (LSA). This study investigated drawings as a tool for use with multilingual children. The participants were 19 children aged 3 to 5 years who used Jamaican Creole and Jamaican English with either typical development (TD, n = 10) or developmental language disorder (DLD, n = 9). Children drew themselves talking, completed the Speech Activity and Participation Assessment of Children (SPAA-C), and provided language samples in both language contexts. Drawings were examined for themes and focal points, the SPAA-C was coded for emotion types, and language samples were analyzed using LSA measures (e.g., mean length of utterance, Index of Productive Syntax). The TD group represented themes more often within their drawings compared to the DLD group. Responses on the SPAA-C were generally positive for both groups. The TD group achieved higher scores across almost all LSA measures compared to the DLD group. The findings suggest that drawings, in concert with LSAs, may be a useful tool in understanding multilingual children's unique communication experiences.
Keywords: developmental language disorder; children's drawings; cultural responsiveness